Manufacturing and characterization of polyether ether ketone/methyl phenyl polysiloxane composite coatings. Issue 26 (24th March 2016) - Barletta, Massimiliano; Gisario, A.; Puopolo, M.; Vesco, S.
ABSTRACT: In this work, manufacturing and characterization of single‐ and multilayer polyether ether ketone (PEEK)‐reinforced coatings were investigated. Hybrid composites of thermoplastic reinforcing agents in a thermoset resin was, therefore, achieved by dispersing large PEEK particles (∼85 μm diameter) in methyl phenyl polysiloxane (MPP). First, mechanism of formation of the polymeric networks during MPP curing at different temperatures (250–400 °C) was analyzed. The different arrangements of the PEEK powders inside the cross‐linked network of the MPP resin were, thus, disclosed. Second, the effect of process parameters on visual appearance, morphological features, and mechanical response of the composite coatings was evaluated by contact gauge profilometry, scanning electron microscopy, IR spectrometry, and microscratch indentations. Moderate temperature curing (250 °C >  T  > 300 °C) of the composite coatings led to polysiloxane resins harder, well adhered on the metal and able to retain better the PEEK reinforce. Further increase in curing temperature (350 and 400 °C) might embrittle the polysiloxane resin, with the PEEK powders in it partially attenuating the loss of properties of the composite coating. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43609. Abstract :